Urgency in Improving Child Health Care Workers' Awareness and Knowledge of ASD: Findings From a Cross-Sectional Study in Southwest China - Ma, Yu; Zhou, Yan; Liu, Ye; Ping, Yue; Wang, Yaozhou; Hu, Xiao; Zhang, Chenxi; Wang, Tianqi; Zhou, Hao (Frontiers in Psychiatry, 2021)
Objective: To evaluate the levels of awareness and knowledge of ASD among child health care workers in China, we conducted a cross-sectional, questionnaire-based study to assess the participants’ awareness and knowledge of ASD. Methods: A total of 159 child health care workers from Southwest China participated in the survey and filled out the questionnaire. Descriptive analysis was conducted on the five parts of the questionnaire, including general knowledge, symptomology, screening and diagnosis, and intervention and treatment. Univariate analysis was used to assess impacts of the participants’ basic demographic characteristics on the questionnaire scores. Multivariate analysis was used to analyze association of the participants’ basic demographic characteristics and the questionnaire scores. Results: Less than 15% of the participants knew that ASD is a developmental, congenital and genetic disorder. Few participants knew that the symptoms include language disorder (38.4%) and social dysfunction (29.6%). A minority of the participants knew the diagnostic criteria (22.6%) and the age for early screening (14.5%). A total of 23.9% of the participants agreed that there are no effective drugs to treat ASD, and 6.3% agreed that ASD is incurable. A number of years in practice of ≥10 (OR=0.3249, 95% CI: 0.1080 - 0.9189) was the main factor related to a high questionnaire score. Conclusions: Most participants had relatively low levels of awareness and knowledge of ASD, especially in terms of general knowledge as well as knowledge of intervention and treatment. Working for more than 10 years was a significant predictor of higher levels of awareness and knowledge of ASD. ASD-related training and knowledge dissemination are crucial for the early diagnosis and intervention of ASD. Child health care workers' awareness and knowledge of ASD needs to be improved to help build public awareness about ASD.